1994
DOI: 10.1103/physrevb.49.4352
|View full text |Cite
|
Sign up to set email alerts
|

Two-magnon light scattering in the layered antiferromagnetNiPS3: Spin-1/2-like anomalies in a spin-1 system

Abstract: Raman spectra of NiPS& (spin S =1) reveal an anomalously broad two-magnon feature whose relative width is comparable to that shown by La2CuO& (S = 2) and other antiferromagnetic copper oxides. The magnetic continuum is strongly coupled to a nearby phonon, whose scattering amplitude interferes with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
13
2

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 27 publications
6
13
2
Order By: Relevance
“…Experimentally, however, no significant change is observed in the continuum scattering over this temperature range. Similarly, the characteristic energy of 2M scattering typically blueshifts considerably as temperature is lowered and evolves into a well-defined peak below T N [42], in contrast to our observations in a-RuCl3 [ Fig. 2(b)], We therefore conclude that spin-phonon coupling does not appreciably damp the magnetic excitations in a-RuCl3.…”
Section: -3contrasting
confidence: 84%
See 1 more Smart Citation
“…Experimentally, however, no significant change is observed in the continuum scattering over this temperature range. Similarly, the characteristic energy of 2M scattering typically blueshifts considerably as temperature is lowered and evolves into a well-defined peak below T N [42], in contrast to our observations in a-RuCl3 [ Fig. 2(b)], We therefore conclude that spin-phonon coupling does not appreciably damp the magnetic excitations in a-RuCl3.…”
Section: -3contrasting
confidence: 84%
“…However, we regard the scenario of heavily damped 2M scattering as unlikely in a-RuCl3 for several reasons. First, the line shape of the magnetic scattering does not change appreciably when going from 100 to 5 K. in contrast to previous reports of phonon-damped 2M scattering [42,43]. For dominant magnon-phonon scattering, the decay rate of a magnon of energy co should be roughly proportional to the thermal occupation factor n(co) + 1 of a phonon of the same energy [43], Taking the magnon energy to be 10 meV (the center of the continuum), this would imply a 20% change in lifetime at low temperature.…”
Section: -3contrasting
confidence: 77%
“…Early Raman studies of NiPS 3 revealed a broad spectral feature at 530 cm Ϫ1 that was originally assigned to electronic scattering 3 but later shown to be due to two-magnon ͑2M͒ excitations. 4 The 2M band exhibits an anomaly in that its linewidth is nearly four times larger than that predicted from standard 2M theory. [5][6][7] The 2M-width anomaly in NiPS 3 is similar to that observed in the parent compounds of the cuprate superconductors.…”
Section: Introductionmentioning
confidence: 92%
“…41 In this context, it is worth noticing that significant spin-phonon coupling recently has been observed in some nonsuperconducting materials. 42,43 We recognize that the phonon renormalization above and below T c may well be coupled and not easily separated. However, to rationalize our observations we will discuss the superconductivity related anomalies and the above T c behavior separately.…”
Section: Discussionmentioning
confidence: 99%